Risk and regulation in research - Savulescu, Julian (Journal of medical ethics, 2015)
One major theme of this issue of the Journal of Medical Ethics is research ethics and its relationship to risk. Unusually, this issue discusses research involving animals as well as human participants. In their editorial, building on two papers in this issue,1 ,2 Yeates and Reed of the RSPCA point out that the public, major funders of animal research, are calling for greater transparency (see page 504).The risk of increased transparency is that it will inhibit research, and therefore limit the potential benefits. Yates and Reed conclude, “That is a reason for improvements, not for a lack of complete transparency.” I would add that better communication of the necessity, the reasonableness of risk and the potential benefits would also help to balance the public's perception of such trials.Having sat on several research ethics committees scrutinising research involving human participants, I have found the balance between protecting participants and facilitating good research is a fine one. I have argued that a pernicious tendency for a legalistic approach to ethical concepts such as informed consent has replaced a genuine consideration of the balance between individual risks and benefits,3 and …